Strategi Pengelolaan Sampah Plastik di Kampung Wisata Arborek Raja Ampat - Macap, Faridz Chalid; Abu, Nur; Dwangga, Mierta; Marasabessy, Umar (Jurnal Teknologi Lingkungan Lahan Basah, 2025)
This study was conducted on the island of Arborek using data determination techniques with observations and questionnaires shared with respondents. The data obtained was then analyzed using SWOT analysis to obtain a plastic waste management strategy. The results of the study showed that the management of plastic waste on the island of Arborek was carried out by the Non-Governmental Organization "Barefoot conservation" involving local people, especially teenagers aged 7-16 years. The management carried out is the collection, sorting, and transportation of waste. then from the results of the questionnaire showed that the response of respondents to the average waste facility assessment score was 3 or a fairly good category. while the response of respondents The average rating score of 4 or categories is not good. The management strategy obtained from the results of the SWOT analysis is to use the WO strategy, which is a progressive strategy that uses the power to seize opportunities or take advantage of opportunities. The strategy is to reduce plastic waste as much as possible starting from the source with the application of 3R methods (reduse, reuse, recycle), and increase the active role of government, community, as well as other parties (private) as managing partners.